A Trigonal‐Pyramidal Erbium(III) Single‐Molecule Magnet1. (24th March 2015) - Brown, Andrew J.; Pinkowicz, Dawid; Saber, Mohamed R.; Dunbar, Kim R.
Abstract Given the recent advent of mononuclear single‐molecule magnets (SMMs), a rational approach based on lanthanides with axially elongated f‐electron charge cloud (prolate) has only recently received attention. We report herein a new SMM, [Li(THF)4[Er{N(SiMe3)2}3Cl]⋅2 THF, which exhibits slow relaxation of the magnetization under zero dc field with an effective barrier to the reversal of magnetization (ΔEeff/kB=63.3 K) and magnetic hysteresis up to 3 K at a magnetic field sweep rate of 34.6 Oe s−1. This work questions the theory that oblate or prolate lanthanides must be stabilized with the appropriate ligand framework in order for SMM behavior to be favored.